Growth, External Debt and Sovereign Risk in a Small Open Economy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper constructs and analyzes an optimizing model of a highly-indebted small open economy. An important innovation in the model is the incorporation of sovereign risk through the specification of an upward-sloping foreign debt supply function. The model is used to examine the interaction between external debt and growth in response to various policies and exogenous disturbances. It is shown that structural policies intended to reduce the fiscal deficit or increase productivity can lead to tradeoffs in their effect on capital accumulation and the stock of debt.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet